(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study explores how the tax avoidance in Bangladesh is influenced by some board characteristics such expertise of board and audit quality, with moderating impact of political connection with board. Using panel data on the banking industry listed on the DSE from 2012 to 2022, the study runs several regressions to investigate whether political connections moderate the board experts. The results revealed that both legal experts and audit quality negatively impact tax avoidance. It indicates that the presence of more legal experts on the board and the greater the use of BIG4 auditors in a firm, the lower their engagement in tax avoidance practices. Accounting experts on the board, conversely, enhance tax avoidance. Similarly, politicians on the board moderate the legal experts and weaken the legal expert’s role regarding tax avoidance decisions. The findings imply that politicians increase tax avoidance by converting the negative role of legal experts into a positive one. Further, supporting agency theory, the findings confirm a conflict between owners and managers where institutional and managerial shareholders dominate the board of directors regarding tax policy.